Conserved forage - Sollenberger, Lynn E.; Reis, Ricardo A. [UNESP]; Nussio, Luiz G.; Chambliss, Carrol G.; Kunkle, William E. (Wiley, 2016)
This chapter focuses on conserving forage as hay or silage. Conserving forage is an essential component of ruminant livestock production systems in most temperate climates, but in subtropical and tropical regions the use of hay and silage is not as widespread. Forage production in warm climates is based on perennial four carbon intermediate grasses. Economic factors are major determinants of the extent to which forage is conserved as hay or silage. Field-cured hay has an important role in feeding ruminant animals in many parts of the world. Defoliation management can be described in terms of frequency, intensity, and timing. Field curing involves both drying and rewetting processes. Hay can be packaged in numerous forms including small and large rectangular bales, small and large round bales, and various stack systems. Silage is the feedstuff produced by the fermentation of a forage crop of high moisture concentration.
Keywords: Conserved forage; Defoliation management; Field-cured hay; Ruminant livestock production systems; Silage production